Gatesina colombiana n. gen. & n. sp. (Hymenoptera: Chalcidoidea, Eurytomidae), new Rileyinae associated with Myrcianthes (Myrtaceae) from Colombia - Cuesta-Porta, Víctor; Caicedo, Guadalupe; Hanson, Paul; Pujade-Villar, Juli (Zootaxa, 2018)
The Neotropical fauna of Chalcidoidea (Hymenoptera) is poorly known, with numerous undescribed species and even genera. Here, we describe a new genus that also includes a new species that parasitizes Eurytominae gall-formers in fruits of Myrcianthes (Myrtaceae) in Colombia. Its conspicuous morphology supports the description of a new eurytomid genus and species, Gatesina colombiana n. gen. & n. sp., belonging to the subfamily Rileyinae. Phylogenetic studies using two matrices of morphological characters as well as molecular data confirm this result. The position of the new genus is close to Neorileya Ashmead according to the phylogenetic analyses.